Salem numbers of automorphisms of K3 surfaces with Picard number $4$ - Lee, Kwangwoo (Comptes Rendus. Mathématique)
We construct automorphisms of positive entropy of K3 surfaces of Picard number $4$ with certain Salem numbers. We also prove that there is a fixed point free automorphism of positive entropy on a K3 surface of Picard number $4$ with Salem degree $4$.